Visible Wireless Communications Using Solitonic Carriers Generated by Microring Resonators (MRRs) - Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Ghasemi, Masih; Ismail, Mohammad Faizal; Azzuhri, Saaidal Razalli; Nayan, Nafarizal; Ahmad, Harith (Springer International Publishing, 2018)
Optical wireless communications (OWC) using soliton pulses in the visible range (600 nm) have been presented. Filtering the input Gaussian spectrum is performed via the microring resonators (MRRs), where the range of 499.25 THz to 500.05 THz frequency band could be generated. The MRRs are simulated using InGaAsP/InP semiconductor with InGaAsP core having refractive index of 3.31 surrounded by InP (n = 3.18). In this research, ten soliton pulses having FSR of 8 GHz were generated at the drop port within the range 499.61 to 499.69 THz frequency band. Here, the generated carriers from the MRRs are modulated with the optical transmitter output which is a laser with extinction ratio of 10 dB and linewidth of 10 MHz utilizing a Mach–Zehnder modulator as an intensity modulator based on an interferometric principle. The frequency and time domain of the transmitted ten soliton carriers through the transmission link are presented as well as the eye diagram.